A 3D-Printed, Metallic-Free, Water-Based Metamaterial for Tunable S-Band Applications - Edoardo Giusti; Danilo Brizi; Agostino Monorchio (IEEE Access)
In this paper, a tunable, water-based S-band metamaterial realized with 3D printing technology and not requiring metallic materials is presented. The proposed structure is capable of reconfiguring between Artificial Magnetic Conductor (AMC) and Radar Absorbing Material (RAM) behaviors, two electromagnetic solutions required in a wide range of applications. The main challenge herein addressed lies in achieving both AMC and RAM configurations by conceiving a 35 mm thick single structure with tunable properties without employing metals and resorting only to Polylactic Acid (PLA) and water, opportunely loaded with sodium chloride (NaCl). The dielectric characteristic of the PLA has been evaluated using a waveguide technique finding a dielectric permittivity of 2.61 and a tangent loss of 0.0327. A multilayer metamaterial structure is designed by exploiting the transmission line equivalent circuit modeling. The switching capability is ensured by controlling the salted water filling of the most external PLA cavity. Accurate numerical simulations carried out with a commercial full-wave software and experimental measurements performed by characterizing the 3D printed prototype within a waveguide demonstrated an excellent agreement and confirmed the validity of the design process. For a normal incidence, the obtained AMC bandwidth is approaching 60% within the S-band, with a maximum loss peak of 3 dB, while the RAM shows a -10 dB absorption fractional bandwidth of 42% centered at 2.8 GHz. The absence of metallic materials in the proposed solution represents a significant advantage compared to traditional AMC/RAM configurations including grounded metallic Frequency Selective Surface patterns in all the applications requiring a high angle stability, where interferences with other devices must be avoided or it is preferrable an environmentally friendly approach.